Uniform Interpretation: Notice of Nonconformity - Mazzotta, Francesco G (Journal of Law and Commerce, 2020)
This Article is about uniform interpretation as it pertains to the nonconformity notices under CISG Article 39.1 Article 39, which is one of the most heavily-litigated provisions of the CISG, provides in relevant part:2 The buyer loses the right to rely on a lack of conformity of the goods if he does not give notice to the seller specifying the nature of the lack of conformity within a reasonable time after he has discovered it or ought to have discovered it. I will focus chiefly on two aspects of Article 39(1): (1) what constitutes a “reasonable time” within which buyers must notify sellers of a “lack of conformity” and (2) what level of specification is required to establish “the nature of the lack of conformity.”